Hyaluronidases improve the hyaluronic acid yield during the fermentation of Streptococcus zooepidemicus - Chuan-Li Kang; Chuan-Li Kang; Chuan-Li Kang; De-Qiang Zheng; De-Qiang Zheng; De-Qiang Zheng; Zhi-Yuan Yao; Kang Yang; Yuxue Zhao; Zihan Mao; Yang Liu; Haijun Li; et al. (Frontiers in Bioengineering and Biotechnology)
BackgroundHyaluronic acid (HA), a linear acidic mucopolysaccharide with exceptional biocompatibility, is extensively utilized in pharmaceuticals and cosmetics. Industrial HA production predominantly relies on Streptococcus zooepidemicus fermentation. However, the accumulation of high-molecular-weight (HMW) HA increases broth viscosity, impeding nutrient diffusion and limiting yield.MethodsTo address this, four HAases, HHya1, LHya2, SHya3, and EHya4, were expressed and screened for enzymatic activity. we evaluated the strategic addition of hyaluronidases (HAases) to degrade HMW HA during fermentation, thereby reducing viscosity and enhancing productivity.ResultsHHya1 and EHya4 exhibited superior expression levels and catalytic efficiency. Purification and functional characterization revealed distinct degradation profiles, HHya1 hydrolyzed HMW HA into saturated tetrasaccharides, while EHya4 generated unsaturated disaccharides. In shake-flask fermentations, supplementation with 1500 U/L EHya4 increased HA titer by 12%, outperforming HHya1. Scaling to bioreactor cultivation with viscosity-controlled HAase dosing further optimized productivity. By administering HAase at intervals corresponding to viscosity thresholds, HA titers reached 10.3 g/L, representing a 14.4% increase over baseline.ConclusionThese findings demonstrate that HAase application alleviates viscosity-associated bottlenecks in S. zooepidemicus fermentations, establishing an optimized process for scalable HA production. This approach balances enzymatic degradation with microbial growth kinetics, offering a practical strategy for industrial HA biosynthesis.